The Rejoining Time of Chromatid Breaks Induced by Gamma Radiation in Vicia faba Root Tips at 3 °C - Savage, J. R. K. (The Rockefeller University Press, 1960)
The observation was made previously that the reduction in radiosensitivity in Vicia faba (as measured by postirradiation root growth) by prolonging the exposure time from about 10 minutes to 24 hours is much less marked at 3°C. than at 19°C. If chromosome damage is mainly responsible for the reduced root growth, this observation might be explained by a smaller drop in the "two-hit" aberration component, resulting from an increased time for which breaks are available for rejoining at 3°C. This hypothesis was tested by comparing chromatid aberration frequencies in root meristem cells produced by 105 rads of (60)Co γ rays, given at dose rates of 19.4 and 0.073 rads per minute. Beans were maintained in aerated water at 2°C. prior to and during irradiation, and at this temperature the rate of development of cells was such that the two different exposure times both occupied a period during which the cell sensitivity was approximately constant. Immediately subsequent to irradiation, the roots were returned to 19°C. and examined cytologically. All chromatid aberrations were less frequent after low dose rate treatment, but only the chromatid interchange reduction was significant. The average time for which breaks are available for reunion, calculated from Lea's G function, was found to be 12 hours (95 per cent C.L. 6 to 24 hours).